Trajectories of General Health Status and Depressive Symptoms Among Persons With Cognitive Impairment in the United States. (August 2022) - Zang, Emma; Guo, Anna; Pao, Christina; Lu, Nancy; Wu, Bei; Fried, Terri R.
Objectives: To identify and examine heterogeneous trajectories of general health status (GHS) and depressive symptoms (DS) among persons with cognitive impairment (PCIs).Methods: We use group-based trajectory models to study 2361 PCIs for GHS and 1927 PCIs for DS from the National Health and Aging Trends Survey 2011–2018, and apply multinomial logistic regressions to predict identified latent trajectory group memberships using individual characteristics.Results: For both GHS and DS, there were six groups of PCIs with distinct trajectories over a 7-year period. More than 40% PCIs experienced sharp declines in GHS, and 35.5% experienced persistently poor GHS. There was greater heterogeneity in DS trajectories with 55% PCIs experiencing improvement, 16.4% experiencing persistently high DS, and 30.5% experiencing deterioration.Discussion: The GHS trajectories illustrate the heavy burden of poor and declining health among PCIs. Further research is needed to understand the factors underlying stable or improving DS despite declining GHS